2010
DOI: 10.1371/journal.pone.0012662
|View full text |Cite
|
Sign up to set email alerts
|

Serosorting Is Associated with a Decreased Risk of HIV Seroconversion in the EXPLORE Study Cohort

Abstract: BackgroundSeroadaptation strategies such as serosorting and seropositioning originated within communities of men who have sex with men (MSM), but there are limited data about their effectiveness in preventing HIV transmission when utilized by HIV-negative men.Methodology/Principal FindingsData from the EXPLORE cohort of HIV-negative MSM who reported both seroconcordant and serodiscordant partners were used to evaluate serosorting and seropositioning. The association of serosorting and seropositioning with HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 21 publications
4
61
1
Order By: Relevance
“…In line with earlier research, however, our data suggest that they remain minority practices, with each being reported by approximately 10% of gay men overall 2 30. Compared with the popularity of serosorting in regular relationships among HIV-negative men and serosorting in casual encounters among HIV-positive men, our findings suggest that these two practices remain supplementary risk-reduction strategies.…”
Section: Discussionsupporting
confidence: 88%
“…In line with earlier research, however, our data suggest that they remain minority practices, with each being reported by approximately 10% of gay men overall 2 30. Compared with the popularity of serosorting in regular relationships among HIV-negative men and serosorting in casual encounters among HIV-positive men, our findings suggest that these two practices remain supplementary risk-reduction strategies.…”
Section: Discussionsupporting
confidence: 88%
“…Researchers focusing on the sexual choices of MSM [15, 16] have found serosorting is associated with decreased risk of HIV infection [17] and changes in the sexual behavior of MSM when it is employed as an HIV risk-reduction strategy [18]. Serosorting has also been documented among HIV-positive PWID [19].…”
Section: Discussionmentioning
confidence: 99%
“…Seroadaptation has been proposed as a way to reduce HIV transmission risk among MSM; however, its effectiveness remains debatable (Cassels, Menza, Goodreau, & Golden, 2009; Philip, Yu, Donnell, Vittinghoff, & Buchbinder, 2010). Seroadaptation practices in our study population were uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed a high prevalence of serodiscordant partnership (69%) and a low rate (59–64%) of protected anal sex with serodiscordant partners, suggesting that serosorting, a form of seroadaptive behaviors, may be less common among HIV+ Asian MSM. For seroadaptive behaviors to be prevalent in a community, there must be frequent and accessible HIV testing, widespread knowledge of HIV transmission risk, and an existing culture of serostatus disclosure (Philip et al, 2010). Such factors are uncommon in the setting of MSM in Thailand.…”
Section: Discussionmentioning
confidence: 99%